Plasma Markers of Neutrophil Extracellular Trap Are Linked to Survival but Not to Pulmonary Embolism in COVID-19-Related ARDS Patients - Prével, Renaud; Dupont, Annabelle; Labrouche-Colomer, Sylvie; Garcia, Geoffrey; Dewitte, Antoine; Rauch, Antoine; Goutay, Julien; Caplan, Morgan; Jozefowicz, Elsa; Lanoix, Jean-Philippe; Poissy, Julien; Rivière, Etienne; et al. (Frontiers in Immunology, 2022)
Introduction: COVID-19 can cause life-threatening acute respiratory distress syndrome (ARDS). Recent data suggest a role for neutrophil extracellular traps (NETs) in COVID-19 related lung damage, partly due to micro-thrombi formation. Besides, pulmonary embolism (PE) is frequent in severe COVID-19 patients, suggesting that immunothrombosis could also be responsible for increased PE occurrence in these patients. Here we evaluate whether plasma levels of NET markers measured shorty after admission of hospitalized COVID-19 patients, are associated with clinical outcomes, in term of clinical worsening, survival and PE occurrence. Patients and Methods: Ninety-six hospitalized COVID-19 patients were included, 50 with ARDS (severe disease) and 46 with moderate disease. We collected plasma early after admission, and measured 3 NET markers: total DNA, myeloperoxidase (MPO)-DNA complexes and citrullinated histone H3. Comparison between survivors and non-survivors and patients developing PE or not were assessed by Mann-Whitney test. Results: Analysis in the whole population of hospitalized COVID-19 patients revealed increased circulating biomarkers of NETs in patients who will die from COVID-19 and in patients who will subsequently develop PE. Restriction of our analysis in the most severe patients, ie the ones who enter the hospital for COVID-19-related ARDS, confirmed the link between NET biomarkers levels and survival but not PE occurrence. Conclusion: Our results strongly reinforce the hypothesis that NETosis is an attractive therapeutic target to prevent COVID-19 progression but that it does not seem to be linked to pulmonary embolism occurrence in patients hospitalized with COVID-19.